Are adult cystic fibrosis patients satisfied with medication treatment? - Esen Deniz Akman; Nadir Yalçın; Oğuz Karcıoğlu; Ebru Damadoğlu; Ali Fuat Kalyoncu; Kutay Demirkan (Orphanet Journal of Rare Diseases)
Abstract Background Treatment satisfaction can be described as the patient’s experience in patients with cystic fibrosis (CF). It can be influenced using modulators and clinical characteristics. The aims of this study were to evaluate and compare adult CF patients with and without modulators regarding treatment satisfaction, related factors and to manage their drug related problems (DRPs). Methods A single-center prospective cohort study was conducted between June 2023 and January 2024. Treatment Satisfaction Questionnaire for Medication (TSQM 1.4), including effectiveness, side effects, convenience, global satisfaction domains, CF Questionnaire-Revised (CFQ-R), and Medication Adherence Report Scale were applied and assessed with and without modulator therapy groups. The relationship between clinical characteristics and TSQM was analyzed by correlations and regression analysis. Recommendations on DRPs identified by clinical pharmacists were made to the physicians and patients and classified according to Pharmaceutical Care Network Europe (PCNE v9.1). Results A total of 110 patients with 51 modulator therapy and 59 without modulator therapy were included. The mean global satisfaction score of modulator users was found to be 19.733 (p < 0.001) points higher than non-users. When the CFQ-R treatment burden score improved by 1point, global satisfaction score increased by 0.233 points (p < 0.001). When the number of hospitalizations increased by 1 day, the global satisfaction score decreased by 4.751 points (p < 0.001). A total of 84 DRPs were identified, and 69 (82.1%) of them were resolved. Conclusions Treatment satisfaction in adult CF patients is influenced by modulators, treatment burden, and clinical factors, so access to modulators is important. This is the first study to classify DRPs according to PCNE in CF. Clinical pharmacists contribute to the management of CF.